Analisis Kesalahan Sintaksis Penerjemahan Siswa SMA Olahraga Negeri Sriwijaya Palembang - Damayanti, Meli (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2017)
The Objective of this study is to describe studentsâ syntactical errors in translation at SMA Olaraga Negeri Sriwijaya Palembang. The method used in this research is qualitative descriptive. Studentsâ translations are collected and then selected purposively by considering the completeness of the translated text component. Techniques used in analyzing the data are, (1) coding the corpus, (2) identifying errors linguistics, especially syntactic errors are found in the corpus; (3) to classifying syntactic errors in the work of translation; After analyzing the data collected, it was found that there are four types of translation error. Those errors are omission error, addition error, disordering errors and substitution error. These errors are typically influenced by the first language or mother tongue which is applied in a second language and also the competence of the students absorb the material given by the teacher.